2011
DOI: 10.1016/j.cub.2011.01.026
|View full text |Cite
|
Sign up to set email alerts
|

High Spontaneous Rate of Gene Duplication in Caenorhabditis elegans

Abstract: SUMMARY Gene and genome duplications are the primary source of new genes and novel functions and have played a pivotal role in the evolution of genomic and organismal complexity [1, 2]. The spontaneous rate of gene duplication is a critical parameter for understanding the evolutionary dynamics of gene duplicates; yet few direct empirical estimates exist and differ widely. The presence of a large population of recently derived gene duplicates in sequenced genomes suggests a high rate of spontaneous origin, also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
142
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(153 citation statements)
references
References 41 publications
8
142
1
Order By: Relevance
“…Recent mutation rate estimates in humans (Itsara et al 2010), S. cerevisiae (Lynch et al 2008), and C. elegans (Lipinski et al 2011) all show an excess of duplicated relative to deleted base pairs. CNVs with allele frequencies ,0.1 from a natural population of D. melanogaster from Raleigh, North Carolina, also reveal a similar 2:1 excess of duplicated sequence (Langley et al 2012).…”
Section: Mutation Rate Estimates For Large Duplications and Deletionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent mutation rate estimates in humans (Itsara et al 2010), S. cerevisiae (Lynch et al 2008), and C. elegans (Lipinski et al 2011) all show an excess of duplicated relative to deleted base pairs. CNVs with allele frequencies ,0.1 from a natural population of D. melanogaster from Raleigh, North Carolina, also reveal a similar 2:1 excess of duplicated sequence (Langley et al 2012).…”
Section: Mutation Rate Estimates For Large Duplications and Deletionsmentioning
confidence: 99%
“…We compared these results to those from two previous studies that were able to estimate the rates of gene duplications and deletions with low-resolution array-based techniques, one in C. elegans (Lipinski et al 2011) and one in S. cerevisiae (Lynch et al 2008). Our estimates of these rates in Drosophila are somewhat higher than those observed in C. elegans (2.2 · 10 27 partially deleted genes/gene/generation; 3.4 · 10 27 partially duplicated genes/gene/generation, according to Lipinski et al 2011), but lower than the rates estimated in S. cerevisiae (3.4 · 10 26 duplicated genes/gene/generation; 2.1 · 10 26 deleted genes/gene/generation, according to Lynch et al 2008). In all three data sets, however, the rate at which new genic copy-number mutations arise is quite high, with approximately one whole-gene duplicate arising per haploid genome every 50-500 generations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, it revealed that gene duplications and deletions are probably more frequent than substitutions (Katju & Lynch, 2003; Lipinski et al., 2011; Lynch et al., 2008; Schrider, Houle, Lynch, & Hahn, 2013). Copy‐number variations (CNV) are indeed ubiquitous in natural populations (e.g., Freeman et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Five lines were identified from each tail of the fitness distribution of a set of~70 MA lines that accumulated mutations for 250 generations; on average, the five 'high fitness' MA lines have threefold higher fitness than the five 'low fitness' lines (Matsuba et al, 2012). Various lines of evidence suggest that the per-genome mutation rate in the base population is unlikely to be much less than one-half nor more than about two per generation (Denver et al, 2004;Phillips et al, 2009;Lipinski et al, 2011;Denver et al, 2012). Provided that the distribution of mutations among lines is Poisson (the standard assumption), it is very unlikely that the different sets of lines differ by nearly as much as threefold in the number of mutations unless the mutation rate itself has evolved.…”
Section: Introductionmentioning
confidence: 99%